miRNAomic Approach to Plant Nitrogen Starvation - Peerzada Yasir Yousuf; Peerzada Arshid Shabir; Khalid Rehman Hakeem (International Journal of Genomics)
Nitrogen (N) is one of the indispensable nutrients required by plants for their growth, development, and survival. Being a limited nutrient, it is mostly supplied exogenously to the plants, to maintain quality and productivity. The increased use of N fertilizers is associated with high-cost inputs and negative environmental consequences, which necessitates the development of nitrogen-use-efficient plants for sustainable agriculture. Understanding the regulatory mechanisms underlying N metabolism in plants under low N is one of the prerequisites for the development of nitrogen-use-efficient plants. One of the important and recently discovered groups of regulatory molecules acting at the posttranscriptional and translational levels are microRNAs (miRNAs). miRNAs are known to play critical roles in the regulation of gene expression in plants under different stress conditions including N stress. Several classes of miRNAs associated with N metabolism have been identified so far. These nitrogen-responsive miRNAs may provide a platform for a better understanding of the regulation of N metabolism and pave a way for the development of genotypes for better N utilization. The current review presents a brief outline of miRNAs and their regulatory role in N metabolism.